2022
DOI: 10.1155/2022/6153279
|View full text |Cite
|
Sign up to set email alerts
|

Oxycodone Alleviates Endometrial Injury via the TLR4/NF-κB Pathway

Abstract: Endometrial injury is a common female disease. This study was designed to illustrate the effects of oxycodone on mifepristone-induced human endometrial stromal cells (hEndoSCs) injury and delineate the underlying molecular mechanism. hEndoSCs were stimulated with mifepristone to generate the endometrial injury in vitro model. hEndoSCs viability, cytotoxicity, and apoptosis were measured by methyl thiazolyl tetrazolium (MTT) assay, lactate dehydrogenase assay (LDH), and flow cytometry (FCM) analysis, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…1 Also, administration of mifepristone could induce the section of inflammatory cytokines (such as TNF-α, IL-β, or IL-6). 11,33 Thus, the levels of TNF-α, IL-β, and IL-6 in hEndoSCs were detected, and consistent with the previous study, 11 the findings indicated that mifepristone promoted TNF-α, IL-β, and IL-6 secretion in hEndoSCs. Oxycodone reduced inflammatory cytokine release in hEndoSCs in a dose-dependent manner, indicating that oxycodone abolished inflammatory cytokine release during mifepristone-triggered hEndoSC damage.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…1 Also, administration of mifepristone could induce the section of inflammatory cytokines (such as TNF-α, IL-β, or IL-6). 11,33 Thus, the levels of TNF-α, IL-β, and IL-6 in hEndoSCs were detected, and consistent with the previous study, 11 the findings indicated that mifepristone promoted TNF-α, IL-β, and IL-6 secretion in hEndoSCs. Oxycodone reduced inflammatory cytokine release in hEndoSCs in a dose-dependent manner, indicating that oxycodone abolished inflammatory cytokine release during mifepristone-triggered hEndoSC damage.…”
Section: Discussionsupporting
confidence: 88%
“…Endometrial injury is a common gynecological disease caused by a variety of factors, including endocrine disorders, inflammation, and abortion, and in severe cases, may cause infertility 1,28 . Our previous research found that oxycodone alleviates endometrial injury via the inhibition of the activation of the TLR4/NF‐kB pathway 11 . However, the function of oxycodone and its latent pathogenesis in endometrial injury have not been completely investigated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations